(untitled) (Journal of Science and Technology, 2016)
Two on-farm experiments were carried out in the coconut belt of Southern Ghana from 2006 to 2009 to evaluate growth of young coconut plantings and nut yield of old coconut fields and their nutrient status under coconut-cassava intercropping systems. Experiment I was carried out in young MYD x VTT coconut plantings. Experiment II was conducted in old West African Tall coconut plantings. The same cropping systems were evaluated under the two experiments in randomized complete block design with two replications each. The cropping systems were: 1. Sole coconut 2. Coconut + non-fertilized cassava 3. Coconut + cassava-fertilizer-I (Fertilizer I= 30- 45-45 kg/ha N-P2O5-K2O) and 4. Coconut + cassava-fertilizer-II (Fertilizer II = 60-45-90 kg/ha N-P2O5-K2O). Young coconut planted as sole crop had significantly (p<0.05) better growth than the intercropped. Coconut intercropped with non-fertilized cassava had superior growth relative to those intercropped with fertilized cassava. There was no significant (p<0.05) difference in growth between coconut intercropped with cassava fertilizer I and those intercropped with cassava fertilizer II. Generally, the nutrient status of young coconut was not significantly (p>0.05) different between the cropping systems. Leaf K was identified as a limiting factor to nut yield in the old coconut plots. Consequently, change in nut yield was closely linked to change in leaf K with high coefficient of correlation (r = 0.798). Old coconut intercropped with fertilized cassava had significant (P<0.05) increase in both leaf K and nut yield while those intercropped with non-fertilized cassava suffered significant (P< 0.05) decline in both leaf K and nut yield.